Role of septal vasopressin innervation in paternal behavior in prairie voles (Microtus ochrogaster). - Wang, Z (1994)
After being paired with females, male prairie voles show major changes in their social behaviors among which is an increase in paternal responsiveness. These changes are accompanied by fluctuations in the density of the [Arg8]vasopressin-immunoreactive (AVP-ir) fibers in the lateral septum, suggesting that septal AVP might be involved in these changes. To explore a possible involvement of septal AVP in paternal responsiveness, we tested whether injections of saline, AVP, or the V1a receptor antagonist [1-(beta-mercapto-beta, beta-cyclopentamethylenepropionic acid),2-(O-methyltyrosine]AVP [d(CH2)5Tyr(Me)AVP] into the lateral septum influenced the four most prominent paternal activities displayed by male prairie voles; grooming, crouching over, contacting, and retrieving pups. In a first experiment, sexually inexperienced males received a single injection of AVP, saline, or d(CH2)5Tyr(Me)AVP in the lateral septum, after which their paternal responsiveness was recorded during a 10-min period. AVP-injected animals spent more time contacting and crouching over pups, while d(CH2)5Tyr(Me)AVP-injected animals spent less time grooming pups than saline-injected animals. In a follow-up study, one group of animals received an injection of AVP preceded by an injection of saline or d(CH2)5Tyr(Me)-AVP into the lateral septum. A second group of animals received an injection of saline preceded by an injection of saline or d(CH2)5Tyr(Me)AVP into the lateral septum. In both groups, animals spent less time grooming, crouching over, and contacting pups if they had first been injected with d(CH2)5Tyr(Me)AVP. Control experiments suggested that the effects of AVP on paternal responsiveness were dose- and site-specific. These data suggest that septal AVP enhances paternal responsiveness by a V1a receptor-mediated mechanism.